Effectiveness of contrast-enhanced ultrasound and serum liver enzyme measurement in detection and classification of blunt liver trauma. (February 2017) - Zhao, Da-wei; Tian, Meng; Zhang, Le-tian; Li, Tao; Bi, Jie; He, Jia-ying; Zhang, Ying-ying
Objective: This study was performed to identify the correlation between contrast-enhanced ultrasound (CEUS) and contrast-enhanced multidetector computed tomography (CE-MDCT) as well as the correlation between serum liver enzyme concentrations and CE-MDCT in classification of the severity of blunt hepatic trauma using CE-MDCT as a reference standard. Materials and methods: A blunt liver trauma model was created using 20 rabbits, and CE-MDCT, CEUS, and serum liver enzyme assays were performed. A radiologist and an ultrasound physician independently evaluated the degree of liver trauma. The diagnostic performance of CEUS and serum liver enzyme measurements was compared with that of CE-MDCT using Spearman's correlation analysis and Pearson's correlation analysis, respectively. Results: Spearman's rank correlation coefficient between the CEUS-based classification and CE-MDCT was 0.888. The aspartate aminotransferase and lactate dehydrogenase concentrations and the aspartate aminotransferase/alanine aminotransferase ratio were positively correlated with the grade of liver injury; Pearson's correlation coefficients were 0.664, 0.704, and 0.503, respectively. The gamma-glutamyltransferase concentration had a significantly negative correlation with the grade of liver injury (r = −0.467). Conclusions: CEUS and serum liver enzyme measurement exhibited high consistency with CE-MDCT for both detection and grading of intraparenchymal lesions in blunt liver trauma. These techniques may permit more accurate diagnosis of liver trauma.